2005
DOI: 10.1186/1477-7819-3-63
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life determinants in women with breast cancer undergoing treatment with curative intent

Abstract: QOL derangements are common in breast cancer patients necessitating the provisions for patient access to psychosocial services. However, because of the huge patient load, a screening process to identify those meriting intervention over the general population would be a viable solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 21 publications
8
26
2
1
Order By: Relevance
“…Verbal stigma ranging from gossip to outright abuse was also described. Similar manifestations are described by a study on breast cancer treatment and social stigma in Thailand [ 41 ], a study on attitudes towards breast cancer among South Asian women living the United Kingdom [ 42 ], a study on quality of life of women with breast cancer in India [ 43 ], a Nigerian study on the psychosocial concerns of women living with breast and cervical cancer [ 44 ], and a Kenyan study on stigma related to both cervical cancer and HIV [ 45 ].…”
Section: Discussionsupporting
confidence: 67%
“…Verbal stigma ranging from gossip to outright abuse was also described. Similar manifestations are described by a study on breast cancer treatment and social stigma in Thailand [ 41 ], a study on attitudes towards breast cancer among South Asian women living the United Kingdom [ 42 ], a study on quality of life of women with breast cancer in India [ 43 ], a Nigerian study on the psychosocial concerns of women living with breast and cervical cancer [ 44 ], and a Kenyan study on stigma related to both cervical cancer and HIV [ 45 ].…”
Section: Discussionsupporting
confidence: 67%
“…The data on occupation of the accompanying person were similar to those in the study by Pandey and colleagues, which also found that the accompanying person tended to be an unemployed spouse or son or daughter 28. In the present study, 80.39% of the accompanying persons were not employed outside the home 28…”
Section: Discussionsupporting
confidence: 88%
“…These findings may be explained by adult children's capacity to provide support to their parent during this difficult time and the patients’ inability to cope with the prospect of leaving their underage children without a parent. Although these findings have not been replicated in other studies, two breast cancer studies found that having underage children was a significant predictor of negative changes in QoL after surgery [21] and those with unmarried children had significantly lower QoL scores [22], which lends credence to our hypothesis.…”
Section: Discussionsupporting
confidence: 39%